Factors associated with body image dissatisfaction and distortion among Iranian women. (August 2016) - Nikniaz, Zeinab; Mahdavi, Reza; Amiri, Samira; Ostadrahimi, Alireza; Nikniaz, Leila
Abstract: The prevalence of body image dissatisfaction is considered high in both developed and developing countries. It has been shown that many factors affect the body image dissatisfaction. However, because of the economical and cultural differences, it seems that these affecting factors should be determined in each region. So, the present study was designed to evaluate the prevalence and associated factors with body image dissatisfaction and distortion among Iranian women. Body image perception was analyzed in 500 women through the Stunkard figure rating system. The International Physical Activity Questionnaire was used for assessing physical activity level. The information about age, marital status and socioeconomic status was recorded by general questionnaire. The one-way ANOVA and regression were used for statistical analysis. By increasing the BMI categories from underweight to obesity, participants tended to perceive their body size thinner than real body size. The regression models indicated that the body image distortion was significantly increased with increasing the BMI (p = 0.002) and physical activity level (p = 0.008). Besides, dissatisfaction by being heavier than ideal was significantly associated with higher BMI (OR (95% CI). 1.21 (1.03, 1.17)). Considering the high prevalence of body image dissatisfaction among Iranian women, for preventing psychological problems and eating disorders, appropriate public health programs for increasing awareness about healthy body size were needed. Highlights: The prevalence and associated factors with body image dissatisfaction and distortion among Iranian women were studied. The prevalence of body image dissatisfaction among Iranian women was high. Even normal weight women were also dissatisfied with their body size. The body image distortion was significantly increased with increasing the physical activity level.